Energy Optimal Control of Electromechanical Systems: Trade-off Demands - Ftorek Branislav; Vavrúš Vladimír; Šimon Ján; Vittek Ján (Power Electronics and Drives, 2025)
This study presents research on the impact of the selection of the required manoeuvre time on the energy consumption of an electromechanical system, using the example of a train. Two different energy conservation control strategies [energy optimal control (EOC) and energy near-optimal control (ENOC)] were applied to assess their consumption as a function of recommended travel time. The optimal control variables are provided by an energy-saving reference position generator, whose outputs are then faithfully followed using a feedback control based on field orientation, and this is accomplished with a matched zero dynamic lag pre-compensator, yielding the required closed-loop dynamics. The load torque, consisting of constant, linear and quadratic components as a function of speed, is treated as a state variable. The potential for energy savings by reducing the speed of such systems was verified through MATLAB simulations. As a representative controlled electromechanical system, a suburban train unit was chosen for simulations to evaluate the energy consumption of both control approaches.